A review on association of mothers’ single Nucleotide Polymorphism (BsmI) of vitamin D receptor gene with risk of preterm birth and low birth weight - Tonmoy, Hasan Shahriyer (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.